The measurement of biaxial strains in coated fabric materials using the disc-replica method - Webb, J.; Richards, D. M. (College of Aeronautics, 1969)
A method of measuring biaxial strains in coated fabric type materials is presented whereby the strain is deduced from the distortion of a circular impression made on the material. The impression is placed on the material when loaded, enabling all measurements to be made with the material in its relaxed, unloaded, state.